Nutraceutical evaluation of hexane-extractable lipid form bika (Ampelocissus martini Planch.) seed oil. - Villanueva, Kriscela Haguisan (2014.)
Bika (Ampelocissus martini Planch.) or wild grape is an endemic species in Southeast Asia. In the Philippines, it is abundant in Panay Island, particularly in the provinces of Antique and Iloilo. Although such fruit is locally consumed as food, such as medicine, and made into wine, very limited scientific studies about it exist. This study focuses on the nutraceutical evaluation of Bika seed oil. The total phenolics content was determiend using the Prussian Blue assay, and it was found out that Bika seed oil has 1,022.197mg Gallic Acid Equivalents/g sample. Bika seed oil also has a high free-radical scavenging activity relative to the standard (Ascorbic acid) used, and this was tested using the DPPH Assay. Flavonoids and tannins were tested qualitatively, and gave positive results. In the determination of fatty acid content using Gas Chromatography, it was found out that the major fatty acids present in the oil include: linoleic acid (48.26 percent), palmitic acid (11.81 percent), stearic acid (9.0 percent), and oleic acid (27.98 percent). In order to determine the oil's shelf-life, its Oxidative Stability Index (OSI) was determiend using the Rancimat method, and obtained OSI value was 7.73(hours). Present results prove that Bika seed oil has a high antioxidant activity and a high Omega-6 content. This means that bika seed oil is a probable raw material for dietary supplements, and cound be used as an alternative for grape seed oil.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Bika -- Seeds; Ampelocissus martini Planch